Prevention of thromboembolic complications in casualties with multiorgan injuries - Gariachy Yevgenеy; Litovchenko, Viktor; Berezka, Mykola (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
Thromboembolic complications (TEC) take one of the first places by the number and severity of complications in severe multiorgan injuries. The purpose of the present work was to assess the efficacy of performing thromboprophylaxis within the remote (more than 5 days) postoperative period and in the outpatient stage of treating casualties with multiorgan injuries. Forty patients were analysed, the overwhelming majority of them, i.e. 25 cases (63 %), sustained a severe concomitant brain and skeletal injury in the form of long bone fractures of their lower extremities. All the patients received prevention of TEC from the first postoperative day. Low-molecular heparin Dalteparin was administered according to the producer’s instructions on the average of 5-7 days and until the casualty regained his consciousness. In order to improve the quality of TEC prevention and ensure observation of their doctors’ orders by the patients, it was recommended to transfer to a tableted anticoagulant Xarelto®: one 10-mg tablet once a day. As a result of the therapy it was found out that, owing to an easy taking of the drug and no necessity to monitor blood coagulation parameters, a full course of prophylaxis was underwent by 34 patients of 40 (85 %). No symptomatic manifestations of TEC were revealed in all the patients at the moment of their examination. No clinically significant specific complications within the period of taking the above drug were detected. Good compliance of patients against a background of using Xarelto® was noticed.